ABCD microstates: a new word in EEG mathematical analysis - A. A. Ivanov (Эпилепсия и пароксизмальные состояния, 2025)
With the advent of computer electroencephalographs, mathematical methods for EEG processing began to actively develop, some of which have found their application in current clinical practice, others – in brain-computer systems, some algorithms are used only in scientific research, whereas the remaining have shown inefficiency and become undemanded. Here, a fairly new approach to the mathematical processing of EEG signals is overviewed that allows not only to diagnose brain functional state, but also to predict the treatment outcomes in critically ill patients in intensive care units. Particularly, ABCD microstates will be discussed.